Implementasi Kuruikulum Merdeka Belajar di Sekolah Dasar - Idha Isnaningrum; Novi Marliani; Saring Ariyanto (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
This research aims to analyze the implementation of the Merdeka Curriculum in Indonesian elementary schools, taking into account various factors such as teacher understanding, school readiness, and student and parent responses. The research method used is literature study, which involves reviewing written sources, such as scientific journals and proceedings, to obtain relevant data and information. The research results show that the Independent Curriculum provides freedom for teachers and students in the learning process, but its implementation is faced with various obstacles, including difficulties in developing appropriate learning and assessment tools. Nevertheless, the Merdeka Curriculum is expected to be able to improve the quality of education by creating a more flexible and relevant learning environment. This research concludes that continuous evaluation and adjustments are needed to overcome existing challenges, so that the Merdeka Curriculum can make a positive contribution to character development and the potential of students and creating the next generation who are ready to face global challenges.